2014
DOI: 10.1017/s0954579414000741
|View full text |Cite
|
Sign up to set email alerts
|

The use of prosody during syntactic processing in children and adolescents with autism spectrum disorders

Abstract: In this study, we employed an eye-gaze paradigm to explore whether children (8-12) and adolescents (12-18) with autism spectrum disorders (ASD) are able to use prosodic cues to determine the syntactic structure of an utterance. Persons with ASD were compared to typicallydeveloping (TD) peers matched on age, IQ, gender, and receptive language abilities. The stimuli were syntactically ambiguous but had a prosodic break that indicated the appropriate interpretation (feel the frog…with the feather vs. feel…the fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 86 publications
0
27
0
1
Order By: Relevance
“…Using a similar paradigm. Diehl et al found that teenagers with ASD were able to efficiently use prosodic cues to constrain their interpretation of sentences like ‘Put the apple on the towel in the box.’ High‐functioning children with ASD also understand the structural restrictions of reflexive pronouns in English (i.e., appropriately distinguishing Bart washed him from Bart washed himself ) and French (i.e., appropriately producing Elle se lave when shown pictures of a girl washing herself, and Elle le lave when shown pictures of the girl washing another). Finally (and allowing us to circle back to the original ‘form is easy’ studies), statistical learning of both artificial grammars and novel speech streams have been assessed in school‐aged children with ASD, and have yielded similarly positive effects as their TD controls (see Ref for a recent meta‐analysis of statistical learning in ASD).…”
Section: Development Of Syntax and Morphology Seems Easymentioning
confidence: 99%
See 1 more Smart Citation
“…Using a similar paradigm. Diehl et al found that teenagers with ASD were able to efficiently use prosodic cues to constrain their interpretation of sentences like ‘Put the apple on the towel in the box.’ High‐functioning children with ASD also understand the structural restrictions of reflexive pronouns in English (i.e., appropriately distinguishing Bart washed him from Bart washed himself ) and French (i.e., appropriately producing Elle se lave when shown pictures of a girl washing herself, and Elle le lave when shown pictures of the girl washing another). Finally (and allowing us to circle back to the original ‘form is easy’ studies), statistical learning of both artificial grammars and novel speech streams have been assessed in school‐aged children with ASD, and have yielded similarly positive effects as their TD controls (see Ref for a recent meta‐analysis of statistical learning in ASD).…”
Section: Development Of Syntax and Morphology Seems Easymentioning
confidence: 99%
“…Using a similar paradigm. Diehl et al 80 found that teenagers with ASD were able to efficiently use prosodic cues to constrain their interpretation of sentences like 'Put the apple on the towel in the box.' High-functioning children with ASD also understand the structural restrictions of reflexive pronouns in English (i.e., appropriately distinguishing Bart washed him from Bart washed himself 81 ) and French (i.e., appropriately producing Elle se lave when shown pictures of a girl washing herself, and Elle le lave when shown pictures of the girl washing another 82 ).…”
Section: Development Of Syntax and Morphology Seems Easymentioning
confidence: 99%
“…Children with ASD have been reported to produce atypical intonation, which has been variably described as sounding Brobotic,^Bmonotone,^Boverprecise,^or Bsing-song^( [18] and references therein), and have difficulties with using intonation appropriately in communication [40]. However, children with ASD may show strong pitch discrimination capacities in both speech and non-speech material [43] and can make use of intonational information to process syntactically ambiguous sentences [19]. These findings suggest that children with ASD and normal (verbal) intelligence can perceive the acoustic differences between monotonous speech and speech with normal intonation and may associate human speakers with speech with normal intonation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some individuals with autism spectrum disorders (ASD) produce speech which lacks the usual acoustic characteristics which mark particular prosodic features; for example, the difference in duration between stressed and unstressed syllables tends to be smaller in the speech of children with ASD (Paul, Bianchi, Augustyn, Klin, & Volkmar, 2008). These prosodic production deficits extend to perception as well: individuals with ASD tend to have difficulty with the perception of prosodic cues to emotion (Globerson, Amir, Kishon-Rabin, & Golan, 2015;Golan, Baron-Cohen, Hill, & Rutherford, 2007;Kleinman, Marciano, & Ault, 2001;Phillip et al, 2010;Rutherford, Baron-Cohen, & Wheelwright, 2002), lexical stress (Kargas, López, Morris, & Reddy, 2016), phrase boundaries (Diehl, Bennetto, Watson, Gunlogson, & McDonough, 2008), and linguistic focus (Peppé, Cleland, Gibbon, O'Hare, & Castilla, 2011) in speech (but see Diehl, Friedberg, Paul, & Snedeker, 2015). These prosody perception difficulties can interfere not only with communication skill and sociability (Paul, Augustyn, Klin, & Volkmar, 2005), but may also increase the risk of delayed language acquisition given the importance of prosody for disambiguating language meaning (Lyons, Simmons, & Streeter, 2014).…”
Section: Prosody and Language Acquisitionmentioning
confidence: 99%